Biosynthesis of iron oxide (Fe2O3) nanoparticles via aqueous extracts of Sageretia thea (Osbeck.) and their pharmacognostic properties. Issue 4 (2nd October 2017) - Khalil, Ali Talha; Ovais, Muhammad; Ullah, Ikram; Ali, Muhammad; Shinwari, Zabta Khan; Maaza, Malik
ABSTRACT: Sageretia thea (Osbeck.) was used as an effective chelating agent for the biosynthesis of iron oxide nanoparticles (IONP's) and extensively characterized through XRD, FTIR, Raman spectroscopy, Energy Dispersive Spectroscopy, HR-SEM/TEM and SAED. Antibacterial assays against five human pathogenic bacterial strains were carried out and minimum inhibitory concentrations were calculated. Pseudomonas aeruginosa (MIC: 7.4 µg/mL) was the most susceptible strain to biosynthesized IONPs. All of the fungal strains showed susceptibility to the IONPs. MTT cytotoxic assay was carried out against the promastigote and amastigote cultures of Leishmania tropica and their IC50 values were calculated as 17.2 and 16.75 µg/mL. The cytotoxic potential was further assessed using brine shrimps, and the IC50 was calculated as 16.46 µg/mL. Moderate antioxidant activities were reported. Human RBCs and macrophages were found to be biocompatible with biogenic IONPs (IC50 > 200 µg/mL). GRAPHICAL ABSTRACT: